2020
DOI: 10.1108/ijchm-06-2019-0522
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the consequences of theme park experience through the lenses of self-congruity and flow

Abstract: Purpose This paper aims to propose and test a conceptual model of theme park experiences by investigating the relationships among brand experience, self-congruity, flow and brand-related outcomes. Design/methodology/approach Data were collected from guests who had visited a theme park in the past 12 months. Confirmatory factor analysis, consisting of second-order factor analysis and structural equation modeling with the incorporation of alternative model testing, was employed. Findings The findings reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…This finding reinforces the important role of commitment to build a larger export market with a business model that is able to overcome export barriers. In line with the findings of Fu et al (2020) corroborating the findings of this study that the experience of managing an amusement park will increase the commitment of visitors, by designing an amusement park that can create value for visitors and be able to immerse visitors to enjoy the place of entertainment optimally.…”
Section: Hypothesis Testing and Sobel Testsupporting
confidence: 90%
“…This finding reinforces the important role of commitment to build a larger export market with a business model that is able to overcome export barriers. In line with the findings of Fu et al (2020) corroborating the findings of this study that the experience of managing an amusement park will increase the commitment of visitors, by designing an amusement park that can create value for visitors and be able to immerse visitors to enjoy the place of entertainment optimally.…”
Section: Hypothesis Testing and Sobel Testsupporting
confidence: 90%
“…Only four papers deal with co-creation, and only two deal specifically with relationships. There is some evidence of methodological development, with increasingly sophisticated analytical techniques being applied in recent years, such as structural equation modelling (Fu, et al , 2020), as well as “natural” methods of data gathering and new methods of data capture, such as wristbands (Stadler et al , 2018). There is also some indication that Pine and Gilmore’s most recent phase of economic development, the idea of transformative experiences, is emerging in the literature (Neuhofer et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…As the research continues to deepen and expand, scholars have found that outdoor recreation can provide participants with a sense of challenge and focus, which coincides with flow characteristics [3,9]. Flow experience has been gradually applied to the research of adventure tourism, theme tourism, mountaineering tourism, and cultural and creative tourism, which shows high participation and strong feelings of experience [1,2,10,11]. In addition, as the state of individual flow comes with a strong sense of participation, such exploratory behaviour will lead to positive behaviours and emotions in individuals [12].…”
Section: Introductionmentioning
confidence: 98%